Co‑Creating Human‑Centred and Responsible AI Gover-Nance in Consulting SMEs - Jiříčková, Ludmila (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
Small and medium-sized enterprises (SMEs) in consulting increasingly rely on AI tools in client work, yet often lack proportionate and human-centred governance approaches that translate high-level “responsible AI” principles into everyday organisational practice. This doctoral research proposes AIROF – an adaptive AI Risk & Opportunity Framework – grounded in fourth-order cybernetics to enable co-created governance through explicit roles, feedback loops, and continuous contextual adaptation. Using a Design Science Research approach, the study synthesises theoretical foundations (AI governance, risk management, Balanced Scorecard logic, fourth-order cybernetics) and triangulates them with empirical insights in consulting SMEs to design and validate AIROF. The planned instantiation (AIROF Scorecard) will support decision-making without requiring disruptive process redesign. This paper contributes a research agenda and evaluation plan for co-creating human-centred, responsible digital futures in resource-constrained knowledge organisations.